The Impact of the Epidemic on Risk-Taking in Commercial Banks - Shuoqi, Yang; Ab Razak, Nazrul Hisyam; Kamarudin, Fakarudin (Journal of Ecohumanism, 2025)
The outbreak of the COVID-19 epidemic in 2020 significantly impacted various industries and the overall economy, with China’s GDP showing negative growth in the first quarter of that year, threatening the banking sector. Despite the limited direct effect on the scale of lending by Chinese commercial banks, non-performing loans experienced a significant increase. This study examines the influence of the epidemic on commercial banks’ risk-taking behavior. It finds that the epidemic enhances risk-taking by increasing economic losses, directly through financial losses and indirectly through rising business risks, reduced profitability, and changes in enterprise cash reserves. Moreover, the study highlights that insurance protection and bank risk management are moderating, with stronger protections weakening the impact on risk-taking. Additionally, the heterogeneity of local banks reveals that those serving rural areas experience greater risk-taking impacts than banks focused on urban industrial and commercial groups.